Pemberdayaan Santri melalui Pelatihan Kaligrafi di Pondok Pesantren Darul Huda Mayak Tonatan Ponorogo - Agustin, Ayu; Soraya, Siti Zazak (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tulungagung, 2022)
Abstract The development of students is critical to be improved through various training so that students like Islamic art in the form of calligraphy art and can preserve it, one of which is calligraphy training. The art of calligraphy can add to the aesthetics of the Qur'an because calligraphy is a reflection of the response to divine messages. The purpose of this community service was to improve the ability of students in the art of calligraphy. The approach used in this service is the ABCD (Asset-Based Community Development) method with students' assets at the Darul Huda Islamic Boarding School Mayak Ponorogo. The enthusiasm of the students was extraordinary. The calligraphy training participants were enthusiastic about participating in the training and producing contested and exhibited works. The evaluation results showed that the calligraphy skills of the participants had increased, and the participants continued to receive training and guidance after the exhibition. Abstrak Pengembangan santri sangat penting untuk ditingkatkan melalui berbagai pelatihan agar santri menyukai seni Islam berupa seni kaligrafi dan mampu melestarikannya salah satunya pelatihan kaligrafi. Seni kaligrafi mampu menambah estetika Al Qur’an karena kali grafi cerminan dari respon terhadap pesan pesan ilahi. Tujuan pengabdian masyarakat ini adalah meningkatkan kemampuan santri di seni kaligrafi. Pendekatan yang digunakan dalam pengabdian ini adalah metode ABCD (Asset Based Community Development) dengan aset santri di Pondok Pesantren Darul Huda Mayak Ponorogo. Antusias para santri sangat luar biasa. Para peserta pelatihan kaligrafi semangat mengikuti pelatihan dan menghasilkan karya yang dilombakan serta dipamerkan. Hasil evaluasi menunjukan kemampuan kaligrafi peserta meningkat dan peserta tetap mendapat pelatihan dan bimbingan pasca pameran kegiatan.